MODEL OF SECONDARY PARAMETERS FOR ASSESSING STATUS OF THE STATE SECRET PROTECTION - Dreis , Yurii (Ukrainian Information Security Research Journal, 2025)
Protection of classified information, especially state secrets, is an important task in the field of national and information security of the state. To minimize possible damage to the national security of Ukraine from violations in the field of state secret protection and to reduce the negative international rating and other serious consequences at the state level, the task of creating specialized databases, developing and improving existing methods and models that implement relevant assessments is urgent. That is why the theoretical multiple presentation of the parameters of the “Report on the State of Protection of State Secrets” in tuple models allows solving the actual scientific and practical task of formalizing the process of assessing the negative consequences of leaking a state secret, its disclosure or loss of Material Carriers of Secret Information (MCSI), violation of the secrecy regime and state of ensuring the protection of country’s secrets in general. Previously, a tuple model of primary and internal parameters was developed, and now, as its completion, a model of secondary parameters and its hierarchical structure has already been proposed, due to the integrated theoretic-multiple representation of sets characterizing information: the implementation or ordering (scientific and/or scientific and technical support) of secret research, development, design and other scientific works, manufacture of secret products, regime premises, objects of information activity, international cooperation, etc., allows to determine sets of input and output parameters for the formation of special databases and formalization of the process of damage assessment caused to national security by violations of state secret protection mechanisms. In the future, to implement the above process, it is necessary to improve the method of assessing damage to national security in the event of a leak of state secrets, both separately for the subject of regime-secret activity (reporting subject) and for the organization (institution) to which the reporting subjects are directly subordinate.